Human resource management - Mondy, R. Wayne 1940- (Prentice Hall, 1999)
Intended for introductory undergraduate/ graduate-level courses in Human Resource Management, this title is a survey of contemporary human resource management. It includes the impact of global competition and rapid technological advances that have accelerated trends such as shared service centers, outsourcing and just-in-time training.